HIV testing preferences among pregnant women attending antenatal care and their male partners: a discrete choice experiment in Uganda. Issue 4 (6th December 2019) - Korte, Jeffrey E; Strauss, Michael; Ba, Aissatou; Buregyeya, Esther; Matovu, Joseph KB; Kisa, Rose; Musoke, William; Chemusto, Harriet; Vrana-Diaz, Caroline J; Malek, Angela M; Wanyenze, Rhoda K; George, Gavin
Abstract : HIV testing rates remain stubbornly low among men – a crucial target population for reaching the ambitious global and regional goals of the HIV programme. In an era of declining donor funding, identifying cost-effective strategies to increase testing rates amongst men remains paramount. Antenatal care is an effective entry-point for the delivery of HIV testing services for women, and partner testing presents an important opportunity to reach their male partners. We present the results of a discrete choice experiment in Uganda, examining preferences among 824 pregnant women and 896 male partners regarding service delivery characteristics of HIV testing. Both men and women preferred nurse administered testing to self-testing (OR = 0.835; p < 0.001), oral testing over a finger-prick test (OR = 1.176 ; p < 0.001) and testing with a partner over testing alone (OR = 1.230; p < 0.001). Men had a preference for testing at home compared to testing at a clinic (OR = 1.099; p = 0.024), but women were indifferent regarding the testing location. The cost of testing had the biggest effect on preferences. Free testing was preferred over a cost of US2.90 (OR = 0.781; p < 0.001) or US2.00 (OR = 0.670; p < 0.001). Offering an incentive of US3.40 increased men's preferences compared to a free test (OR = 1.168; p < 0.001), although this did not affect women's preferences. Partner testing linked to antenatal care is a potential strategy to increase testing coverage among men, particularly given the preference for partner testing – provided costs to clients remain low. Future cost-effectiveness evaluations should investigate the economic impact of reaching men using these strategies.